EFEKTIFITAS MERONCE BALOK HURUF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK TUNAGRAHITA RINGAN - Ima Kristin Handayani, Asep Ahmad Sopandi, Martias. Z (Universitas Negeri Padang, 2013)
This research is motivated by problems of mild mental retardation children who have problems in reading the word. This study aims to prove the effectiveness of panning bar letters to improve reading skills noun. The research methodology is Single Subject Research with ABA design. Results showed stable to unstable to stable. Based on these results it can be concluded that the panning bar letters effective in improving the reading ability of the child mild mental retardation a second class in SLB Luki Padang.